A Study on the Effectiveness of Using Digital Material of Podcast to Improve Students’ Speaking Ability - Rahmi Aulia Amir; Chairil Anwar Korompot; Sultan Baa (Journal of Excellence in English Language Education, 2023)
This study aimed to assess whether the use of podcasts to improve students' speaking ability is effective. The speaking ability measured consisted of five levels: pronunciation, intonation, fluency, accuracy, and comprehension. This study was designed as a pre-experiment one group pre-test and post-test which involved 30 students at the class XI MIPA 1, SMAN 9 Sinjai, Sinjai. Research data was collected using a speaking test. Data were analyzed with descriptive statistics and paired samples test using SPSS type 16.00. A significant level was determined at α = 0.05. The result of the study indicated that the use of digital material podcasts is effective in improving students’ speaking ability. The students achieved better speaking ability and reached higher post-test scores on average. It indicates that the implementation of the digital material podcast had a significant effect on students’ speaking ability, which includes pronunciation, intonation, fluency, accuracy, and comprehension. Based on the results of the research, it can be concluded that the use of digital material podcasts was effective in improving the students’ speaking ability. The findings suggest that the process of speaking after the podcast was implemented can develop students’ speaking ability. Future research could discuss the results of a test conducted to investigate the effectiveness of the digital material of podcast approach based on the student’s favorite types of podcasts.